2015
DOI: 10.1111/nmo.12618
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal gas content and distribution in health and in patients with functional gut symptoms

Abstract: Azpiroz ABSTRACTBackground. The precise relation of intestinal gas to symptoms, particularly

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
37
1
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(42 citation statements)
references
References 27 publications
3
37
1
1
Order By: Relevance
“…The increase in gas content observed was probably related to the arrival into the colon of complex carbohydrates resistant to small bowel digestion. The amount of colonic gas and the intraluminal distribution of the gaseous mass, both during basal conditions as well as after eating lettuce, was within the normal range observed in healthy subjects during fasting and after a regular meal …”
Section: Discussionsupporting
confidence: 65%
“…The increase in gas content observed was probably related to the arrival into the colon of complex carbohydrates resistant to small bowel digestion. The amount of colonic gas and the intraluminal distribution of the gaseous mass, both during basal conditions as well as after eating lettuce, was within the normal range observed in healthy subjects during fasting and after a regular meal …”
Section: Discussionsupporting
confidence: 65%
“…An experimental gas challenge test (high-rate exogenous gas infusion directly into the jejunum) has shown that patients with functional dyspepsia who complain of bloating have impaired handling of intestinal gas, that is, gas retention, abdominal symptoms or both 165 . However, studies using abdominal CT and MRI scanning in clinical conditions could not corre late abdominal symptoms with excessive intestinal gas in these patients, as in the majority of the patients the volume and distribution of intestinal gas were within the normal ranges 166,167 . Hence, the perception of abdominal bloating could be related to a poor tolerance of normal gut content.…”
Section: Gas-related Symptomsmentioning
confidence: 82%
“…Visible distension is frequently associated with a bloating sensation, but the reverse is not the rule. Patients who complain of postprandial distension indeed develop an increment in girth during the distension episodes compared with basal conditions, but the volume of gastrointestinal gas is by and large within the normal range 167 . Furthermore, this abnormal distension is produced by a paradoxical diaphragmatic contraction, which is associated with a relaxation of the anterior abdominal wall 169 .…”
Section: Abdominal Distensionmentioning
confidence: 94%
“…Unfortunately, the mechanistic insight on the generation of small bowel‐related visceral hypersensitivity and its contribution to abdominal pain and other main symptoms in IBS is much more limited than for the colon. In this sense, mechanical distension induced by increased and/or abnormal distribution of intestinal gas has been related to spontaneous bloating and ingestion of flatulogenic diet in some IBS patients . Similarly, increased activation and release of mast cell products have been shown to increase and potentiate alterations in permeability and intrinsic and afferent neurons, thereby leading to enhanced visceral pain perception in both the small bowel and the colon .…”
Section: Introductionmentioning
confidence: 99%